2019
DOI: 10.1155/2019/1314028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Decision Support System in Back Pain Diagnoses: A Pilot Study

Abstract: It is the main goal of this study to investigate the concordance of a decision support system and the recommendation of spinal surgeons regarding back pain. 111 patients had to complete the decision support system. Furthermore, their illness was diagnosed by a spinal surgeon. The results showed significant medium relation between the DSS and the diagnosis of the medical doctor. Besides, in almost 50% of the cases the recommendation for the treatment was concordant and overestimation occurred more often than un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 21 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Every age group is affected by back pain. The incidence of low back pain is 60-90%, and low back pain is the main cause of working disability in most countries [6][7][8][9][10]. Also neck pain is in increasing problem with incidences of between 10.4% and 71.5%, and an annual prevalence varying between 30 and 50% [7,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Every age group is affected by back pain. The incidence of low back pain is 60-90%, and low back pain is the main cause of working disability in most countries [6][7][8][9][10]. Also neck pain is in increasing problem with incidences of between 10.4% and 71.5%, and an annual prevalence varying between 30 and 50% [7,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these enormous costs for the health care system, more and more attempts are made to support health care providers with a computerized decision support systems (DSS). The DSS can be considered as one specific form of a symptom checker [ 10 ]. The study group of the authors has already developed and published a first use of a computerized algorithm which is based on the next best questions to find out the most possible diagnosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the use of AI-based algorithms in a diagnostic decision support system (DDSS) can be seen as another potential of AI in medicine. Data has already shown that such a DDSS can help patients to estimate the severity of their complaints and can also be useful to support medical personnel [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%